(untitled) (Research, Society and Development, 2020)
The diversity of neoplasms observed in dogs can vary geographically depending on individual susceptibility, the habitat of the animals, and environmental characteristics. The aim of this study was to evaluate the epidemiological aspects of neoplasms in dogs treated at the Veterinary Hospital of the State University of Maranhão from 2008 to 2015. We studied the medical records of 1089 dogs affected by neoplasms and treated at a hospital during the period of study, relating to the casuistry with their breed, age, sex and origin. The present study included 764 cases that were confirmed through cytopathology. The most prevalent tumors were transmissible venereal tumors (TVT) (20.17%), adenocarcinoma of the mammary gland (19.53%), mixed malignant tumor of the mammary gland (18.63%), mast cell tumor (11.31%), and mammary carcinoma (6.42%). Females with a mean age of 9.2 years were the most affected, as were SRDs, Poodles, American Pitbulls, and Dobermann Pinschers. According to the cytomorphogenetic classification, the round cell tumors were the most prevalent, with values close to those of epithelial, followed by mixed and mesenchymal cells.